Preface to Special Issue of ChemSusChem—Water Splitting: From Theory to Practice. Issue 9 (18th April 2019) - Tilley, S. David; Selloni, Annabella; Hisatomi, Takashi
Abstract: In this Editorial, Guest Editors David Tilley, Annabella Selloni, and Takashi Hisatomi introduce the Special Issue of ChemSusChem on Water Splitting: From Theory to Practice. The significance and enormous challenges of sunlight‐driven water splitting are reviewed and the contents of the contributions to the Special Issue are outlined. Abstract : Make like a banana and split : In this Editorial, Guest Editors David Tilley, Annabella Selloni, and Takashi Hisatomi introduce the Special Issue of ChemSusChem on Water Splitting: From Theory to Practice. The significance and enormous challenges of sunlight‐driven water splitting are reviewed and the contents of the contributions to the Special Issue are outlined.